Global suburbs : urban sprawl from the Rio Grande to Rio de Janeiro - Herzog, Lawrence A. (Lawrence Arthur) (New York : Routledge, 2015)
"Global Suburbs: Urban Sprawl from the Rio Grande to Rio de Janeiro offers a critical new perspective on the emerging phenomenon of the global suburb in the western hemisphere. American suburban sprawl has created a giant human habitat stretching from Las Vegas to San Diego, and from Mexico to Brazil, presented here in a clear and comprehensive style with in depth descriptions and images. Challenging the ecological problems that stem from these flawed suburban developments, Herzog targets an often overlooked and potentially disastrous global shift in urban development. This book will give depth to courses on suburbs, development, urban studies, and the environment"--
Includes bibliographical references and index.
Keywords: Suburbs -- North America; Suburbs -- South America; Cities and towns -- North America; Cities and towns -- South America; Cities and towns -- Growth -- Environmental aspects -- North America; Cities and towns -- Growth -- Environmental aspects -- South America; SOCIAL SCIENCE / Sociology / General